2006
DOI: 10.1086/499235
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Mass of the Ultraluminous X-Ray Source M82 X-1

Abstract: We report the first clear evidence for the simultaneous presence of a low-frequency break and a QPO in the fluctuation power spectrum of a well-known ultraluminous X-ray source (ULX) in M82 using long XMM-Newton observations. The break occurs at a frequency of 34.2+6-3 mHz. The QPO has a centroid at νQPO=114.3+/-1.5 mHz, a coherence Q≡ν_QPO/ΔνFWHM~=3.5, and an amplitude (rms) of 19% in the 2-10 keV band. The power spectrum is approximately flat below the break frequency and then falls off above the break frequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 27 publications
1
113
1
Order By: Relevance
“…Dewangan et al (2006a) used this proportionality for ULX X-1 in M82 and found the mass of the BH to be in the range of (25−520)M ⊙ . We used the same scaling argument to approximate the mass of the BH in X-2 of NGC 4736.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Dewangan et al (2006a) used this proportionality for ULX X-1 in M82 and found the mass of the BH to be in the range of (25−520)M ⊙ . We used the same scaling argument to approximate the mass of the BH in X-2 of NGC 4736.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Their X-ray luminosities (Colbert & Mushotzky 1999;Kaaret et al 2001), thermal disk emissions (Kaaret et al 2003), variation timescales (Strohmayer & Mushotzky 2003;Dewangan et al 2006), and surrounding emission-line nebulae (Pakull & Mirioni 2003;Kaaret et al 2004b) suggest that they might have masses of 20-10 3 , falling into the class of intermediate-mass black M , holes (IMBHs). However, if the emission is beamed (King et al 2001;Körding et al 2002) or exceeds the Eddington limit (Begelman 2002;Ebisawa et al 2003), some or all ULXs may be stellar-mass black holes.…”
Section: Fabbiano and White 2006) Many Ulxs Show Strong Variabilitymentioning
confidence: 99%
“…If PBHs can grow sufficiently by accretion (or if they are very large at birth), they may account for intermediate-mass black holes (IMBHs) in the mass range 10 2 M P M P10 4 M , which have been suggested as the engines behind ultraluminous X-ray sources (ULXs) recently discovered in nearby galactic disks (Dewangan et al 2006;Madhusudhan et al 2006;Miller 2005;Mushotzky 2004). On the basis of the observed ULX luminosities of $10 39 erg s À1 , stellar-mass black holes are ruled out unless the emission is highly beamed; there is at present no evidence for beaming (Mushotzky 2004;Freeland et al 2006;Poutanen et al 2007;Miniutti et al 2006).…”
Section: Introductionmentioning
confidence: 99%